Inhibitory Effects of Brazilian Propolis on Lipid Accumulation in 3T3-L1 Cells - Yasuhito Nobushi; Naoki Oikawa; Yuzo Okazaki; Shigetoshi Tsutsumi; Yong Kun Park; Masahiko Kurokawa; Ken Yasukawa (Journal of Pharmacy and Nutrition Sciences, 2014)
We here investigated the inhibitory effect of Brazilian propolis on intracellular lipid accumulation. Seven ethanolic extracts of Brazilian propolis were tested for their inhibitory effect on intracellular lipid accumulation in 3T3-L1 cells. Among the seven Brazilian propolis, the extracts AF-08 and AF-18 had inhibitory effects on intracellular lipid accumulation. In particular, the Brazilian propolis AF-08 exhibited a potential inhibitory effect on intracellular lipid accumulation.Thus, these results suggest that the Brazilian propolis AF-08 contributes to the prevention of metabolic syndrome. In addition, five known triterpenoids were isolated from the Brazilian propolis AF-08: betulonic acid, moronic acid, 3-oxo oleanolic acid, masticadienonic acid, and anwnweizonic acid. Four of the triterpenoids exhibited an inhibitory effect on intracellular lipid accumulation. Thus, these triterpenoids may be important as antiobesity agents that inhibit the metabolic syndrome.